Natural volatility, welfare and taxation - Olaf Posch; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2006)
Cyclical components are analytically computed in a theoretical model of stochastic endogenous fluctuations and growth. Volatility is shown to depend on the speed of convergence of the cyclical component, the expected length of a cycle and on the altitude of the slump. Taxes affect these channels and can therefore explain cross-country differences and breaks over time in volatility. With exogenous sources of fluctuations, a special case of our model, decentralized factor allocation is efficient. With endogenous fluctuations and growth, decentralized factor allocation is inefficient and (time-invariant) taxes can (de-) stabilize the economy. No unambiguous link exists between volatility and welfare.
Keywords: C65; E32; E62; H3; O33; 330; Konjunktur; Konjunkturtheorie; Steuererhebung; Wohlfahrtseffekt; Stochastisches Wachstumsmodell